Perfectionism and contemporary feminist values - Yuracko, Kimberly A., 1969- (Book collections on Project MUSE., 2003)
Although formal barriers to women's social and political participation have crumbled, society remains, to a significant degree, gendered in the roles that women and men play. Women's and men's choices regarding work and family are largely responsible for maintaining and reinforcing the differences. While feminists recognize the need to criticize women's choices, too often they focus on restrictive conditions rather than the choices themselves. Kimberly A. Yuracko argues instead that encouraging women to m.